PREFERENCES FOR REDISTRIBUTION AND PERCEPTION OF FAIRNESS: AN EXPERIMENTAL STUDY. Issue 4 (August 2014) - Durante, Ruben; Putterman, Louis; van der Weele, Joël
Abstract We conduct a laboratory experiment to study how demand for redistribution of income depends on self‐interest, insurance motives, and social concerns relating to inequality and efficiency. Our choice environments feature large groups of subjects and real‐world framing, and differ with respect to the source of inequality (earned or arbitrary), the cost of taxation to the decision maker, the dead‐weight loss of taxation, uncertainty about own pretax income, and whether the decision maker is affected by redistribution. We estimate utility weights for the different sources of demand for redistribution, with the potential to inform modeling in macroeconomics and political economy